Injuries to standing passengers using different handrails in subway train collision accidents. Issue 1 (2nd January 2021) - Yao, Shuguang; Li, Xiangyu; Xiao, Xianliang; Xu, Ping; Che, Quanwei
Abstract: Subway collision accidents are inevitable, and if an accident occurs, it can cause injuries to passengers. In this study, the finite element method is used to compare four different situations with forward standing and lateral standing: back constraints with handrails I, II and III and hand constraints with handrail I. The results show that in the case of standing backward, handrail III can cause serious head, neck and leg injuries to passengers, while handrails I and II can cause only leg injuries. In the case of holding the handrail, standing in the forward direction will significantly reduce injury, while standing sideways will cause serious head and chest injuries to the passengers. This study can provide a reference for the safety design of the interior of subway cars and for passengers standing in subway trains.